Effect of herpes simplex virus infection on murine antibody-dependent cellular cytotoxicity and natural killer cytotoxicity. - Kohl, S (1981)
Mice intraperitoneally inoculated with a sublethal dose of herpes simplex virus (HSV) produced immunoglobulin G antibody-dependent cellular cytotoxicity (ADCC) and radioimmunoassay (RIA) antibody as early as 3 days after infection. There was a rise in natural killer cytotoxicity (NKC) to infected and uninfected target cells 1 to 3 days postinfection mediated by nonadherent peritoneal cells (PC) in mice inoculated with HSV, but also with other substances commonly used in tissue culture media. HSV caused the highest and most consistent increase in NKC. PC-NKC, as ADCC, was inhibited by latex and silica, both macrophage inhibitors. PC-ADCC markedly declined 3 to 8 days after HSV inoculation. This was not due to a soluble or cellular suppressor factor, was not reversed by incubation or trypsin treatment of PC, was not associated with a change in PC Fc receptors, adherence, or acridine orange staining characteristics, and could not be induced by inactivated HSV. In vitro inoculation of PC with HSV similarly caused a reduction in the ability of PC to mediate ADCC to HSV-infected target cells. These data demonstrate the complex stimulatory and inhibitory interactions between virus and host defense mechanisms.